The Effect of Harmonic Ability Exercises on 110m Hurdles Performance Among Physical Education and Sport Science Students - Iftekar Matar Baqir; Zana Hashim Ismael; Mohammed Layth Mohammed (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This study aims to determine the most important harmonic capabilities in the effectiveness of the 110m hurdles event and to investigate whether these capabilities are positively influenced by a structured program of harmonic ability exercises among Physical Education and Sport Science students. An experimental design with control and experimental groups was employed. Ten students from the College of Physical Education and Health Sciences (Al-Mustaqbal University) were randomly selected and equally divided into two groups of five each. A four-week harmonic ability exercise program was implemented with the experimental group, comprising two sessions per week. Pre-tests and post-tests of 110m hurdles performance were conducted, and data were analyzed using arithmetic mean, standard deviation, Pearson correlation, skewness coefficient, and paired samples t-test. Statistically significant differences were found between the pre-test and post-test results of the experimental group in 110m hurdles performance (p < 0.05), while the control group showed no significant improvement. The experimental group demonstrated meaningful advancement in achievement levels compared to the control group. Purposefully designed harmonic ability exercises significantly accelerate the development of coordination and performance in the 110m hurdles among Physical Education and Sport Science students. These exercises are recommended for integration into teaching and training curricula.